MENGGAGAS TAFSIR EMANSIPATORIS DALAM AL-QUR’AN (PERSPEKTIF PEMIKIRAN AMINAH WADUD DALAM BUKU AL-QUR’AN WAL MAR’AH) - Siti Majidah; Rizki Firmansyah (Academic Journal of Islamic Principles and Philosophy, 2021)
This study aims to present Aminah wadud's interpretation of the Qur'anic view of women which according to her is quite relevant to be studied. Aminah Wadud tries to initiate an emancipatory interpretation of gender equality in human relations without being distinguished by gender. This type of research is library research with a descriptive analysis approach. The writer uses descriptive analysis approach to get a comprehensive understanding and point of view. The conclusion of this study shows that the Qur’an is actually able to adapt subtly to the conditions of women in this contemporary era as fourteen centuries ago where it was able to acculturate nicely with the Arab nation culture. Aminah sees that in the teachings of Islam (the Qur'an) there is no single value that discriminates against the role and position of women. In fact, according to him, many interpretations of gender bias are the source of this discrimination. Because Aminah Wadud tries to give interesting ideas related to women's interpretation using a Holistic approach, namely rereading the text independently without being influenced by several traditionalistic interpretation styles that are widely used by male interpreters.